Iron metabolism in Pseudomonas aeruginosa biofilm and the involved iron-targeted anti-biofilm strategies. (16th March 2021) - Zhang, Yapeng; Pan, Xuanhe; Wang, Linqian; Chen, Liyu
Abstract: Pseudomonas aeruginosa is a gram-negative bacterium that exists in various ecosystems, causing severe infections in patients with AIDS or cystic fibrosis. P. aeruginosa can form biofilm on a variety of surfaces, whereby the bacteria produce defensive substances and enhance antibiotic-resistance, making themselves more adaptable to hostile environments. P. aeruginosa resistance represents one of the main causes of infection-related morbidity and mortality at a global level. Iron is required for the growth of P. aeruginosa biofilm. This review summarises how the iron metabolism contributes to develop biofilm, and more importantly, it may provide some references for the clinic to achieve novel anti-biofilm therapeutics by targeting iron activities.